But What Are Students REALLY Thinking When They Do Research? - Michael Fosmire (Issues in Science and Technology Librarianship)
The article explores what students are really thinking when they engage in research projects or when they solve information intensive problems using think aloud verbal protocols. Topics covered include Verbal Protocol Analysis (VPA), the applications of the think-aloud protocol in the library literature and getting complementary information by using think-aloud protocols in combination with other techniques.